Reduced Glutamatergic Currents and Dendritic Branching of Layer 5 Pyramidal Cells Contribute to Medial Prefrontal Cortex Deactivation in a Rat Model of Neuropathic Pain - Kelly, Crystle J.; Huang, Mei; Meltzer, Herbert; Martina, Marco (Frontiers in Cellular Neuroscience, 2016)
Multiple studies have demonstrated that neuropathic pain is associated with major reorganization in multiple brain areas. In line with the strong emotional salience of chronic pain, involvement of the limbic system appears particularly important. Within the past few years, it has become clear that the functional deactivation of the prefrontal cortex is critical for both the cognitive/emotional and the sensory components of pain. However, at the cellular level, details of this deactivation remain in large part unclear. Here we show that one week after a peripheral neuropathic injury (Spared Nerve Injury model) pyramidal cells in layer 5 of the rat medial prefrontal cortex show responses to excitatory glutamatergic inputs that are reduced by about 50%, as well as reduced frequency of spontaneous excitatory synaptic currents. Additionally, these cells have reduced membrane capacitance and increased input resistance. All these findings are consistent with decreased dendritic length, thus we performed a detailed morphological analysis on a subset of the recorded neurons. We found that the apical dendrites proximal to the soma (excluding the tuft) are shorter and less complex in SNI animals, in agreement with the reduced capacitance and glutamatergic input. Finally, we used in-vivo microdialysis to compare the basal concentrations of glutamate and GABA in the prefrontal cortex of sham and SNI rats and found that ambient glutamate is decreased in SNI rats. Taken together, these data show that impaired glutamatergic transmission contributes to the functional deactivation of the mPFC in neuropathic pain. Additionally, the reduced branching of apical dendrites of layer 5 pyramidal neurons may underlay the gray matter reduction in chronic pain.